2013
DOI: 10.1016/j.jana.2012.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Digital Gaming for HIV Prevention With Young Adolescents

Abstract: The search for intervention strategies appropriate for young adolescents has recently led to the use of digital games. Digital gaming interventions are promising because they may be developmentally appropriate for adolescent populations. The gaming approach also capitalizes on an inherent interest to adolescents and circumvents traditional barriers to access to prevention interventions faced in some geographical areas. Notwithstanding, research on gaming in HIV prevention is quite limited. In this review artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 3 publications
1
21
0
Order By: Relevance
“…6 The use of educational games for adolescents has shown that playful and participatory work fosters arguments, reflections and collective construction of knowledge among them. [7][8] Therefore, it becomes relevant to unleash efforts for the production and validation of educational technologies directed to this public.…”
Section: Introductionmentioning
confidence: 99%
“…6 The use of educational games for adolescents has shown that playful and participatory work fosters arguments, reflections and collective construction of knowledge among them. [7][8] Therefore, it becomes relevant to unleash efforts for the production and validation of educational technologies directed to this public.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated by participants, the informational needs of a young adolescent 12 year old sexually inexperienced boy would be different for the needs of a middle adolescent 16 year old sexually active girl. Including different levels in an HIV prevention game that are accessed based on characteristics (i.e., sex, age, level of sexual experience) identified in the game and build on feedback from the individual player would enhance relevance (Enah et al, 2013). In more general terms, gaming intervention developers need to carefully consider the balance between potential user’s needs for information, desire for entertainment and the goal of the game to enhance health.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasingly earlier onset of puberty documented in recent decades, young adolescents face the potential of spending many years with a sexually mature body and ‘sexually activated brain circuits with relatively immature neurobehavioral systems’ necessary for anticipating the potential long-term consequences of early sex (Enah, Moneyham, Vance, & Childs, 2013; Rew & Bowman, 2008; Steinberg, 2007). Young adolescents, therefore, need venues to observe and reflect on the long-term consequences of current sexual risk behaviors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The low cost of such media (especially compared to in-person sexual health education by teachers and health care providers) makes it a costeffective platform for delivering sexual health interventions. 5 In particular, gamification (i.e., the use of gaming components such as rewards, competition and interactivity) has been shown to: increase sexual health knowledge, 6 reduce sexual stigma and sexual risk behaviours, [7][8][9] and have a wide reach. 10 Based on a randomized control trial, the virtual reality game PlayForward: Elm City Stories had a positive association between greater progress through the game and the sexual health knowledge score among 11-14 year olds.…”
mentioning
confidence: 99%